Dampak Pandemi Covid-19 Terhadap Efektivitas Pembelajaran Jarak Jauh Secara Daring - Sri Herwanto Dwi Hatmo (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
This research reviews the impact of the Covid-19 pandemic to the effectiveness of online distance learning. It seeks the degree of students’ material understanding via online learning in each region, with the availability and limitations of different internet network connections. This condition is used as a reference that whether online learning method bring useful results compared to face-to-face methods. This situation will also be reflected in students’ opinion when asked about the effectiveness and preference of the learning method. The samples were taken purposively for an electronic questionnaire survey through Google Form. The results indicated that: 1)the transition from face-to-face learning methods (81.8%) to online distance learning (PJJ) (18.2%) has an effect on understanding the absorption of material; 2) the occurrence of constraints caused by the condition of the infrastructure, as the main medium the quality is not guaranteed, namely internet connection (42.9%), resulting in less effective online learning activities.